2006
DOI: 10.4028/www.scientific.net/kem.312.111
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Evolution of Microvoids in Particle-Filled Polymers under Plate Impact

Abstract: Statistical evolution of microvoids in a particle-filled polymer under plate impact is theoretically studied. Based on the constitutive equations of the material recently obtained by the authors, the velocity of the propagation of one-dimensional strain wave caused by the plate impact is analyzed, and the evolution of the microdamage is calculated. It is shown that the microvoid evolution is influenced by several factors, such as particle size-dispersity, average radius of particles, and the adhesive energy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Recently, more attentions are paid to the study of the toughness, the constitutive models, and the mechanism of dynamic failure of the materials by many researchers [1][2][3][4]. It is found that the evolution of microvoids (nucleation, growth and eventually coalescence of microvoids) is the main mechanism of failure of the materials [5][6]. Because the nucleation of microvoids is induced by the interfacial debonding between particles and the matrix of materials, the effects of external influences, the properties of matrix, and the shape and size of the particles on the interfacial debonding should be studied carefully.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, more attentions are paid to the study of the toughness, the constitutive models, and the mechanism of dynamic failure of the materials by many researchers [1][2][3][4]. It is found that the evolution of microvoids (nucleation, growth and eventually coalescence of microvoids) is the main mechanism of failure of the materials [5][6]. Because the nucleation of microvoids is induced by the interfacial debonding between particles and the matrix of materials, the effects of external influences, the properties of matrix, and the shape and size of the particles on the interfacial debonding should be studied carefully.…”
Section: Introductionmentioning
confidence: 99%